Importance of workstation design and good posture. - Párraga Velásquez, Maria del Rosario (2001)
The human factor is the most important component in the work system. The security and commodity are aspects that should be remembered to obtain a good performance. The workstation design should be in such a way that let the users and enable them to achieve a relationship so that the users will not be disturbed by the equipment they are using with their work make easier its work. Also, they may avoid inadequate postures that cause injury in operators working functions.